(untitled) (Latakia University Journal - Economic and Legal Sciences Series, 2019)
يتلخص هذا البحث في النقاط التالية: - توضيح الأسس النظرية التي يقوم عليها الترويج الدوائي، والخصوصية التي ينفرد بها هذا المنتج، وبيان دور أهم المؤثرات البيعية في ترويجه وتصريفه. - إظهار أهم العوامل المؤثرة في اختيار المزيج الترويجي الدوائي، والتي باعتمادها يمكن الوصول لاتباع سياسة ترويجية ناجعة وسليمة في تسويق المنتجات الدوائية السورية. - التعرض لواقع النشاط الترويجي في منشآت الصناعة الدوائية السورية، والتعرف على أهم العناصر والأساليب الترويجية المتبعة فيها، وذلك للتمكن من الوقوف على أهم المعوقات التي تحول دون الوصول إلى سياسة ترويجية مناسبة. - مقارنة ما هو كائن بما يجب إن يكون لاستخراج النتائج وتقديم بعض المقترحات التي من شأنها تفعيل دور النشاط الترويجي في تسويق المنتج الدوائي السوري وتصريفه. This research can be summarized as follows: • It clarifies the theoretic bases on which medicinal promotion is based and the specific quality of this product, together with the elements affecting its circulation and disposal. • It presents the most effective factors in choosing the medical promotion mixture whose adoption might help to follow a beneficial and safe promotion policy in marketing the Syrian therapeutic products. • It introduces the promotion activity in the Syrian medicinal firms and identifies the most important elements and promotion procedures followed in order to be able to inspect and examine all the obstructions that prevent reaching a suitable promotion policy. • It compares what exists with what should exist, so as to extract the results and give some suggestions which can activate the promotion spirit in marketing the Syrian therapeutic products.